Construction of linear differential equations of the fermenter shell of arbitrary shape in the ultrasonic field - Мельник, Виктория Николаевна; Карачун, Владимир Владимирович (Technology audit and production reserves, 2014)
A computational model of an elastic interaction of the external ultrasonic radiation with the fermenter body is constructed. The linear differential equations of a thin shell under the assumption of arbitrary shape of the ultrasonic beam, which subsequently allow to determine the coordinate functions of the shell along its length, along a parallel and transversely are composed. A system of linear differential equations of the dynamics of the fermenter shell was constructed. As a special case, equations of classical cylinder were obtained. To find the coordinate functions, approximate integration methods, in particular, the variable separation method, are used. The nature of the appearance of active energy state zones in the culture broth due to the radiation of sound waves by the fermenter body is explained. Conditions for the occurrence of local features in the liquid at the resonance level in the form of two caustic surfaces, concentric with the body - large and small radius were analytically outlined. Studies are related to the pharmaceutical industry, production of liquid medications. The results allow the process automation, product quality improvement and productivity increase.